GENUINE PROGRESS INDICATORS SEBAGAI PENDEKATAN ALTERNATIF MENUJU EKONOMI BERKELANJUTAN - LM Syuhada Ridzky; La Ode Agus Said; Siti Kadri Yanti Sari (Halu Oleo University, 2023)
This article aims to discuss how measuring economic growth such as GDP or GRDP in the context of a region no longer translates the reality of society. Using a literature review approach, this article explains how the Genuine Progress Indicator (GPI) can be the latest alternative towards a sustainable economy. There are two important findings from this analysis: first, GPI can act as a catalyst for a paradigm change in understanding economic growth holistically. Second, this change in mindset will be a reference for policymaking that supports the green economic agenda and accelerates the transition to renewable energy.